Senegal : Third Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria: Staff Report; Informational Annex; Press Release; and Statement by the Executive Director for Senegal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses key findings of the Third Review Under the Policy Support Instrument for Senegal. All end-December 2011 quantitative assessment criteria were met-except one on the overall fiscal balance, which was missed by a small margin. Some progress was achieved in structural reforms but a number of benchmarks were missed. The new authorities have confirmed their commitment to the objectives of the program. IMF staff recommends completion of the review and supports the waiver for nonobservance of the end-December 2011 assessment criterion on the overall fiscal deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet